2016
DOI: 10.1002/da.22519
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prevention of Depression and Anxiety in Youth: Test of Cross-Over Effects

Abstract: Anxiety and depression are highly comorbid and share several common etiological processes. Therefore, it may be more efficient to develop interventions that treat or prevent these problems together rather than as separate entities. The present meta-analytic review examined whether interventions for children and adolescents that explicitly targeted either anxiety or depression showed treatment specificity or also impacted the other outcome (i.e., cross-over effects). We addressed this question both within the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 125 publications
1
35
1
Order By: Relevance
“…Evidence of cross-over effects from CATCH-IT suggests that this prevention intervention, which was developed to address risk for depression only, may in fact target shared underlying mechanisms for both depression and anxiety. These results are counter to Garber et al [ 41 ], who, in a meta-analysis exploring cross-over effects for depression and anxiety treatment and prevention interventions, reported no evidence of cross-over effects for depression prevention programs. It is possible that the recruitment process, intervention engagement, and motivational interviews that accompany the CATCH-IT intervention, all of which emphasize building resilience, managing stressors, and working toward goals in addition to preventing low mood and depression, may help teens to generalize depression prevention skills to other distressing symptoms such as anxiety.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Evidence of cross-over effects from CATCH-IT suggests that this prevention intervention, which was developed to address risk for depression only, may in fact target shared underlying mechanisms for both depression and anxiety. These results are counter to Garber et al [ 41 ], who, in a meta-analysis exploring cross-over effects for depression and anxiety treatment and prevention interventions, reported no evidence of cross-over effects for depression prevention programs. It is possible that the recruitment process, intervention engagement, and motivational interviews that accompany the CATCH-IT intervention, all of which emphasize building resilience, managing stressors, and working toward goals in addition to preventing low mood and depression, may help teens to generalize depression prevention skills to other distressing symptoms such as anxiety.…”
Section: Discussioncontrasting
confidence: 91%
“…In fact, clinical research confirms that many treatments developed for depression also result in decreased symptoms of anxiety. One meta-analysis [ 41 ] reviewing randomized clinical treatment or prevention trials found that crossover effects were present in both depression treatments and anxiety treatments, although the effects were stronger for the targeted symptoms. That is, depression treatments had a greater effect on depressive symptoms than anxiety symptoms, and anxiety treatments had a greater effect on anxiety symptoms than depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Youth suicide attempt was significantly correlated with a lifetime anxiety disorder in eight out of 13 studies, in meta-analytic review (Schaffer et al, 2015). Comorbid depression and anxiety disorders (Garber et al, 2016) were most prevalent among youth with suicidal behavior in a sample of Hungarian outpatients (Csorba, Dinya, Plener, Nagy, & Páli, 2009). Out of multiple psychiatric disorders assessed by the MINI, psychotic disorders emerged as an independent predictor of lifetime suicidality, and youth with a suicide attempt history had 6.7 greater odds of psychotic disorder compared with youth who did not (Kinyanda et al, 2011).…”
Section: Predictors Of Youth Suicidal Behaviorsmentioning
confidence: 99%
“…Transdiagnostic approaches are developed based on the common comorbidity of these disorders and the similarities between the disorders in terms of etiology, risk factors, and treatment strategies [15,17]. Crossover effects from prevention programs that focus exclusively on either anxiety or depression further support the idea of targeting both symptom categories with the same intervention [18]. There are few studies of such interventions for youth, but the results to date are generally promising [19][20][21][22].…”
mentioning
confidence: 99%